Utilization of Emulgel Watermelon (Citrullus lanatus) Flesh Extract as a Topical Antioxidant - Yati, Kori; Nugrahaeni, Fitria; Melinda, Rika; Wati, Lilis Rokimah (Borneo Journal of Pharmacy, 2024)
The flesh of watermelon (Citrullus lanatus) contains carotenoid compounds that act as antioxidants. The purpose of this study was to determine the variation in the concentration of carbopol 940 on physical properties, irritation tests, and the stability of emulgel antioxidants against temperature and storage time. Evaluation of the physical properties of C. lanatus pulp extract emulgel includes organoleptic, homogeneity, dosage pH, dispersion, adhesion, emulsion type, viscosity as well as hedonic test and irritation test. Antioxidant stability testing of emulgel was carried out for 28 days at three temperature conditions: 4, 25, and 40°C and tested on days 0, 7, 14, 21, and 28 with the DPPH method. The results of the physical properties evaluation meet the requirements with pH values of 5.50–5.57, dispersion 5–6 cm, adhesion <4 seconds, viscosity 5624–15443 cPs, F2 and F3 hedonic tests are preferred by researchers, and irritation tests of all formulas show no irritation symptoms to all refiners. The results of antioxidant stability of emulgel after storage on the 28th day showed an average result of IC50 temperature of 4°C (112.4547 ± 0.1432 mg/L), 25°C (119.3170 ± 0.1966 mg/L), and 40°C (124.1554 ± 0.1317 mg/L). The results of stability analysis show that temperature and storage duration affect antioxidant stability. The higher the temperature and duration of storage, the antioxidant stability of emulgel decreases. Storage of C. lanatus flesh extract emulgel at 4°C was able to maintain antioxidant activity for 28 days of storage.